Unveiling Historical Laws of the Rise and Fall of Human Civilization and Pointing to Path for Civilization Advancement: Theoretical Connotation and Practical Value of the Global Civilization Initiative - Xiang, Gao (Napredak, 2024)
Analyzing strategic advantages and the depth of the Global Civilization Initiative and its role in the modernization of humanity, through the practice of the Chinese path and respect for diversities, the author offers a scientific vision of further development of the planet and directions of progress. The opening of the ancient Silk Road provided important channels for the exchange of cultures, goods and information between the East and the West, laying a strong foundation for further cooperation of civilizations. Even after numerous social, political and economic changes in the international environment, China remains firm in pursuing independent foreign politics of peace, vigorously advocating Five Principles of Peaceful Coexistence ad for continued expansion of friendly exchanges and mutually useful cooperation with the countries throughout the world which have different cultures and ideologies. The global security deficit can be solved only through honest understanding and respect, and that is why China insists on mutual consultation and understanding with the promotion of shared progress through cooperation.